Efektivitas Metode Discovery dan Problem Basic Learning dalam Meningkatkan Kualitas dan Output pembelajaran IPAS Kelas V - Hidayatulloh, Uzair Hasan; Anshori, Isa (DIMAR: Jurnal Pendidikan Islam, 2024)
This study examines the effectiveness of Discovery Learning and Problem-Based Learning (PBL) methods in improving the quality and learning outcomes of grade V students in IPAS (Natural and Social Sciences) subjects. Using a quasi-experimental approach as well as a nonequivalent control group design, this study was conducted at MIN 4 Jombang with 64 students divided into experimental (n=34) and control (n=30) groups. Data collection can be done with pretest-posttest assessments, learning quality questionnaires, and observation sheets. The results of this study showed a very significant difference between the two methods, where the Discovery Learning class achieved a higher average posttest score (89.12) than the PBL group (85.33). In addition, the learning quality questionnaire showed that the Discovery Learning group had higher scores in the aspects of motivation, activeness, and participation than the PBL group. Statistical analysis using t-test proved a significant difference between the two groups (t=3.214, p=0.002). This study found that the greater effectiveness of Discovery Learning in encouraging independent exploration and creating a deeper understanding, which has a positive impact on the quality and learning outcomes of students in IPAS subjects.